2019
DOI: 10.1080/21645515.2019.1603985
|View full text |Cite
|
Sign up to set email alerts
|

Trends in varicella and herpes zoster epidemiology before and after the implementation of universal one-dose varicella vaccination over one decade in South Korea, 2003–2015

Abstract: Background: In South Korea, the one-dose varicella vaccine was included in the National Immunization Program for children aged 12-15 months in 2005, and the vaccine coverage reached >95%. The impact of varicella vaccination on varicella and herpes zoster (HZ) was investigated, accounting for demographic changes over time. Methods: We calculated the crude and age-sex standardized incidence rates (IRs) and age-specific IRs of varicella and HZ from 2003 to 2015, using the National Health Information Database incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
2
27
1
Order By: Relevance
“…The present study clearly showed that the age of varicella patients who presented to our ED has increased since the implementation of the universal two-dose VarV. Previous studies also reported that the occurrence of varicella has shifted to older children [9,20]. Qin et al reported the shift of varicella to older children after the implementation of one-dose VarV in Lu'an,…”
Section: Annual Estimated Vaccination Rate In Kobe City and Annual Vasupporting
confidence: 66%
See 1 more Smart Citation
“…The present study clearly showed that the age of varicella patients who presented to our ED has increased since the implementation of the universal two-dose VarV. Previous studies also reported that the occurrence of varicella has shifted to older children [9,20]. Qin et al reported the shift of varicella to older children after the implementation of one-dose VarV in Lu'an,…”
Section: Annual Estimated Vaccination Rate In Kobe City and Annual Vasupporting
confidence: 66%
“…Currently, 33 countries and regions have introduced the universal VarV since 2014 [19]. The effectiveness of the VarV was proven in many countries, and a dramatic decline in the incidence of varicella has been reported [5][6][7][8]20].…”
Section: Annual Estimated Vaccination Rate In Kobe City and Annual Vamentioning
confidence: 99%
“…But it is questionable whether the exposure (vaccination) information in the control group of their previous study was representative of that in the population at risk where cases arose. For example, Choi et al 6 pointed out the problem as follows: “the vaccination rates in cases and controls were 76% and 78%, respectively, which was much lower than the results (> 95%) of the nationwide vaccination surveys.” Using the raw data from the authors' case-control study, 3 we have examined how the effectiveness of the varicella vaccine would have changed if the authors had used an alternative population-based (not patient-based) control group with a vaccination rate similar to the nationwide averages (i.e., ≥ 90%; 88.3%–91.7% in 2007 and 98.9% in 2012) around their study period. 2 12 Table 1 shows that while the crude effectiveness of the varicella vaccine is 12% when the vaccination rate in the control group is 78% as in the authors' previous study, it ranges from 65% to 90% when the vaccination rate in the alternative population-based control group increases from 90% to 97%.…”
mentioning
confidence: 99%
“…The authors said that “In Korea - where one-dose of varicella vaccination for all children aged 12–15 months was recommended by the National Immunization Program (NIP) in 2005 … the incidence rate of varicella has been continuously rising from 22.4 per 100,000 persons to 154.8 from 2006 to 2017.” 1 Based on the varicella incidence statistics, the authors further said that “a universal one-dose varicella vaccination program may have limited effectiveness to decrease in the incidence rate of varicella …” However, we think that the authors should have cautiously used and interpreted the varicella incidence statistics because the statistics were based on the data from the National Notifiable Disease Surveillance System (NNDSS) in which only varicella cases notified by medical doctors and other responsible persons were included and counted. In fact, in contrast to the argument of the authors, utilizing more nationally representative data (i.e., the claims data from the National Health Insurance Review and Assessment Service [NHIRAS]), both Choi et al 6 and Jung et al 7 have demonstrated that the incidence rate of varicella has substantially decreased in Korea (e.g., from 5.71/1,000 person-years in 2004 to 1.87/1,000 person-years in 2015) after the introduction of the varicella NIP in 2005. Like Jung et al, 7 we think that the seemingly increasing incidence rate of varicella with the NNDSS data is a result of an improvement in doctors' reporting rate of national notifiable infectious diseases, 8 including varicella rather than an actual increase in varicella incidence during 2006–2017 in Korea.…”
mentioning
confidence: 99%
“…Human vaccines & immunotherapeutics demonstrated that the incidence rate of varicella decreased 67% after universal one-dose varicella vaccination in South Korea. 1 Another cohort study by Cheng et al demonstrated that the incidence rate of varicella decreased 82.8% after universal one-dose varicella vaccination in Taiwan. 2 Some points needs to be discussed.…”
Section: Recently One Cohort Study Conducted By Choi Et Al Published Inmentioning
confidence: 99%